BIMBINGAN MEMBACA AL-QUR’AN (BMQ) DENGAN METODE DIROSA UNTUK MEMBERANTAS BUTA HURUF HIJAIYAH DI DESA BENTENG - Patimah, Siti; Wulandari, Dyah (Jurnal Pengabdian dan Kewirausahaan, 2022)
Qur'an reading guidance is a program that aims to make people able to read hijaiyah letters. This is done as one of the steps to eradicate hijaiyah illiteracy that occurs among mothers in Benteng Village, Campaka District, Purwakarta Regency. From the results of observations, it is known that there are 24 people who do not know the hijaiyah letter. Based on this, the action of guidance on reading the Qur'an with the dirosa method was carried out for 4 meetings, starting with pre-test and post-test. The alternative chosen to facilitate the learning process in Qur'an reading guidance is to use a special method, namely the DIROSA method (adult Qur'an Education) for the people of Benteng Village, Campaka District, Purwakarta Regency. The conclusion from the implementation of this activity, namely through the BMQ program, the ability to read hijaiyah letters, the ability to show hijaiyah letters randomly and the ability to read hijaiyah letters with fathah, kasroh, and sukun have increased. From 62.1% of those who couldn't do it, it fell to 30.3%, those who could do it 34.84% increased to 62.1%, and 62.1% of those who were able to do it increased to 7.5%. This data shows a significant increase after the guidance on reading the Qur'an in Benteng Village, Campaka District, Purwakarta Regency was carried out. This guidance activity to eradicate hijaiyah illiteracy is very much needed to be able to create a society that is literate in hijaiyah letters.